Deep electrical imaging of the extinct oceanic ridge in the southwestern sub-basin of the South China Sea - Gao, Yan; Li, Jianping; Li, Fuyuan; Zhang, Ruwei; Zhao, Yunsheng; He, Zhanxiang (Frontiers in Marine Science, 2023)
he resistivity structure of an extinct mid-ocean ridge is significant in understanding the evolution of a mid-ocean ridge from its spreading phase to its dying phase. The magnetotelluric (MT) method is a crucial tool in studying the deep resistivity structure as it is sensitive to resistivity which is affected by heat and allows for imaging of the electrical properties of the mantle. While modern electromagnetic data has enhanced our understanding of the deep structure of rapidly expanding and ultra-slow expanding mid-ocean ridges, the deep electrical structure below extinct mid-ocean ridges has not been studied extensively.In July 2020, marine MT instruments were deployed in the southwest subbasin of the South China Sea to study the resistivity structure below a stalled mid-ocean ridge. The study found that the imaged thickness of the lithospheric lid (>100Ωm) varies between 20 and 90 km, exhibiting a positive correlation with its age. The melt ascent channel is closed below the stalled mid-ocean ridge, and the melt falls back and forms a small melt trap below the dead mid-ocean ridge. In the northwest survey line of oceanic ridge, huge low-resistivity anomalies (<1Ωm), located between 80km and 160 km depth. In the southeast survey line of oceanic ridge, there is a slightly smaller low-resistivity anomalies (<1Ωm). These results indicate that partial melt continues to exist after the cessation of spreading at the mid-ocean ridge. The lithosphere-asthenosphere boundary (LAB) and the ocean basin of the South China Sea experienced a certain magmatic transformation during the cooling and falling process. According to the resistivity, temperature, pressure, and SEO3 model, the melt content is estimated to be approximately 1-12%. The electrical structure of the mantle in the South China Sea is an important basis for studying the current state beneath the ceased spreading mid-ocean ridge.